2012
DOI: 10.1016/b978-0-12-394309-5.00006-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell Biology of Ischemia/Reperfusion Injury

Abstract: Disorders characterized by ischemia/reperfusion (I/R), such as myocardial infarction, stroke, and peripheral vascular disease, continue to be among the most frequent causes of debilitating disease and death. Tissue injury and/or death occur as a result of the initial ischemic insult, which is determined primarily by the magnitude and duration of the interruption in the blood supply, and then subsequent damage induced by reperfusion. During prolonged ischemia, ATP levels and intracellular pH decrease as a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
1,622
3
30

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,752 publications
(1,670 citation statements)
references
References 491 publications
(740 reference statements)
15
1,622
3
30
Order By: Relevance
“…In the present study the ventilation of the patients remained constant, so that it was not a possible error factor when the acid-base balance was analyzed, and the intraoperative diuresis was similar for the survivor and nonsurvivor groups. In addition, the patients of both groups had similar times of cold and warm ischemia 23 .…”
Section: Resultsmentioning
confidence: 97%
“…In the present study the ventilation of the patients remained constant, so that it was not a possible error factor when the acid-base balance was analyzed, and the intraoperative diuresis was similar for the survivor and nonsurvivor groups. In addition, the patients of both groups had similar times of cold and warm ischemia 23 .…”
Section: Resultsmentioning
confidence: 97%
“…We showed that increased NF-κB signaling activity conferred neuroprotection in N2a and murine primary neurons. NF-κB is a master regulator of inflammation and immune responses [21]. It is potently activated in brain tissues from stroke patients and ischemic insulted animals [22].…”
Section: Discussionmentioning
confidence: 99%
“…Ek olarak, Ca 2+ artışı hücreyi nekroza, apoptoza ve otofajiye götürür. [3][4][5][6][7] Şiddetli iskemi süresince adenozin trifosfat [adenosine triphosphate; (ATP) kullanılarak adenozin difosfat [adenosine diphosphate; (ADP)]'a, ADP ise adenozin monofosfat [adenosine monophosphate; (AMP)]'a ve sonra sırasıyla adenozin, hipoksantin, ksantin ve inozin gibi pürin metabolitlerine yıkılır. Normal koşullarda hipoksantin ksantin dehidrojenaz ile ürik aside dönüş-türülür.…”
Section: İskemi̇/reperfüzyon Zedelenmesi̇unclassified